Effect of anti-sclerostin antibody on orthodontic tooth movement in ovariectomized rats - Hyunna Ahn; Wonse Park; Sung-Hwan Choi; Namki Hong; Jisun Huh; Seoyeon Jung (SpringerOpen, 2024)
Abstract Background This study aimed to evaluate the effect of systemically administered anti-sclerostin antibodies (Anti-Scl Ab) on orthodontic tooth movements (OTM) in an ovariectomized rat. Methods Twenty-four 12-week-old female Sprague-Dawley rats were randomly divided into two groups: (1) ovariectomy (OVX) group, (2) ovariectomy + romosozumab (ROMO) group. OTM was performed 8 weeks after OVX. The ROMO group received subcutaneous injections of romosozumab twice a week, starting two weeks after OVX. Eight weeks after the OVX, an orthodontic force of 50 g was measured and applied by connecting orthodontic elastic bands between the maxillary first molar and a mini-screw to facilitate tooth movement (orthodontic treatment). Subsequently, the three rats were sacrificed on days 5, 7, 10, and 14. The plaster models were scanned to measure the amount of tooth movement. The effects on alveolar bone and periodontal tissues were evaluated through micro-computed tomography (micro-CT) analysis, tartrate-resistant acid phosphatase (TRAP) staining, and immunohistochemistry (IHC) analysis. Results The ROMO group showed more tooth movement on day 7 of orthodontic treatment. Conversely, on days 10 and 14, relatively less movement was observed. Analysis of the root furcation area of the maxillary first molars revealed that from the 7th day, BV/TV, Tb.N., Tb.Th. increased, while Tb.Sp. decreased in the ROMO group. More TRAP-positive cells were observed in the compression side of the OVX group, the ROMO group exhibited a marked decrease in the positive expression of the RANKL, OPG, and sclerostin. The OPG/RANKL ratio showed significant differences in expression between the two groups. The ROMO group exhibited a higher OPG/RANKL ratio than the OVX group, and the tension side exhibited a higher OPG/RANKL ratio demonstrating significant differences. Conclusion Romosozumab initially accelerated tooth movements, but later decreased tooth movement. As new alveolar bone is formed, the micro-CT parameters are also improved. Osteoclasts, RANKL, OPG, and sclerostin decreased, while the OPG/RANKL ratio became higher.